Case report: Surgical treatment of a primary giant epithelioid hemangioendothelioma of the spine with total en-bloc spondylectomy - Ge, Wanbao; Qu, Yuan; Hou, Tingting; Zhang, Jiayin; Li, Qiuju; Yang, Lili; Cao, Lanqing; Li, Jindong; Zhang, Shanyong (Frontiers in Oncology, 2023)
Epithelioid hemangioendothelioma (EHE) is an exceptionally rare malignant tumor arising from vascular endothelial or pre-endothelial cells. Herein, we report a case of a 43-year-old male patient diagnosed with primary giant spinal EHE and treated with total en-bloc spondylectomy (TES). He presented to our hospital with chronic and progressive back pain. Physical examination results suggested weakened sensation of acupuncture and touch of the left costal arch; the relatively fatal neurological functions had been completely preserved. Radiological examinations indicated a giant destructive soft tissue lesion occupying the T8 vertebral region, accompanied by moderate destruction of the pedicle and lamina, and the 7th left rib. Preoperatively, a biopsy was conducted on the 8th vertebra and resultant pathology led to EHE diagnosis. EHE of left ribs and T8 ribs was confirmed by postoperative immunohistochemical and pathological reports. The patient underwent 7th left rib resection and posterior pedicle screw fixation with 8 pairs of screws and a titanium mesh cage. Subsequently, the TES surgery T8 on the patient’s chest was performed. However, following surgery, he did not undergo radiation or chemical adjuvant treatment. The patient had a disease-free and relapse-free postoperative course for 3 years. TES is safe, effective, and reliable for EHE treatment. However, this patient needs long-term follow-up to evaluate the clinical outcome.